2005
DOI: 10.1093/humrep/dei442
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting endometrial and subendometrial blood flow measured by three-dimensional power Doppler ultrasound during IVF treatment

Abstract: Endometrial blood flow in IVF treatment was negatively affected by serum E2 concentration only.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(21 citation statements)
references
References 36 publications
0
20
0
1
Order By: Relevance
“…One study showed that neither age nor type of infertility affected endometrial or subendometrial blood flow [22]. However, other studies have shown that the FI is significantly lower among women older than 31 but significantly higher in mothers.…”
Section: Discussionmentioning
confidence: 99%
“…One study showed that neither age nor type of infertility affected endometrial or subendometrial blood flow [22]. However, other studies have shown that the FI is significantly lower among women older than 31 but significantly higher in mothers.…”
Section: Discussionmentioning
confidence: 99%
“…97 It has also been reported that endometrial and subendometrial blood flows are negatively affected by serum estradiol concentrations, but they are not affected by other factors, such as women age, smoking habits, or types of infertility or parity, during IVF treatment. 98 This fact could explain that ovarian hyper-responders tend to have lower endometrial and subendometrial blood flows during the early luteal phase (+2 hCG day). 99 We have observed that endometrial FI is significantly decreased after pituitary suppression with a long GnRH protocol.…”
Section: Dsjuogmentioning
confidence: 99%
“…De telles anomalies expliquent la survenue de ménométrorragies en l'absence de lésion intracavitaire, en particulier dans le cas des myomes interstitiels et sous-séreux ne déformant pas la cavité. Les données de l'échographie-doppler retrouvent également une modification de la vascularisation utérine en cas de présence du myome au profit du myome et au détriment de l'endomètre adjacent [17,18].…”
Section: Anomalies De La Vascularisation De L'utérusunclassified